2014
DOI: 10.1534/g3.113.009522
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Activated Beta-Catenin to Identify Wnt Pathway Target Genes inCaenorhabditis elegans, Including a Subset of Collagen Genes Expressed in Late Larval Development

Abstract: The Wnt signaling pathway plays a fundamental role during metazoan development, where it regulates diverse processes, including cell fate specification, cell migration, and stem cell renewal. Activation of the beta-catenin−dependent/canonical Wnt pathway up-regulates expression of Wnt target genes to mediate a cellular response. In the nematode Caenorhabditis elegans, a canonical Wnt signaling pathway regulates several processes during larval development; however, few target genes of this pathway have been ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 68 publications
(106 reference statements)
7
49
0
Order By: Relevance
“…Temporally, however, COL-41 appears to be a larval-specific cuticle collagen, with expression absent from embryos and adults. This result is consistent with RNAseq analyses that demonstrate a peak of col-41 expression in L2 (Gerstein et al, 2010; Jackson et al, 2014). Expression of the fluorescent marker may be visible later than the peak in mRNA expression due to the time lag for protein synthesis and maturation, and/or perdurance of the mCherry protein.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Temporally, however, COL-41 appears to be a larval-specific cuticle collagen, with expression absent from embryos and adults. This result is consistent with RNAseq analyses that demonstrate a peak of col-41 expression in L2 (Gerstein et al, 2010; Jackson et al, 2014). Expression of the fluorescent marker may be visible later than the peak in mRNA expression due to the time lag for protein synthesis and maturation, and/or perdurance of the mCherry protein.…”
Section: Resultssupporting
confidence: 90%
“…Collagen is secreted from the apical surface of the epidermal cells to the exterior of the body. Cuticle collagen genes show highly specific temporal expression patterns that may be stage-specific or cycle in phase with the cuticle molts (Jackson et al, 2014; Johnstone and Barry, 1996; Park and Kramer, 1994). Additionally, levels and timing of cuticle collagen gene expression respond to cell signaling pathways, such as the TGFβ and Wnt pathways (Jackson et al, 2014; Liang et al, 2007; Roberts et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…First, we showed that the L4 col genes col-38, col-49, and col-71 are regulated by the Wnt pathway transcription factor BAR-1 (beta-catenin) (Gorrepati et al, 2015;Jackson et al, 2014;Van Der Bent et al, 2015), which binds to its target genes via interaction with the TCF transcription factor POP-1 (Jackson & Eisenmann, 2012). First, we showed that the L4 col genes col-38, col-49, and col-71 are regulated by the Wnt pathway transcription factor BAR-1 (beta-catenin) (Gorrepati et al, 2015;Jackson et al, 2014;Van Der Bent et al, 2015), which binds to its target genes via interaction with the TCF transcription factor POP-1 (Jackson & Eisenmann, 2012).…”
mentioning
confidence: 99%
“…*p 0.01 and **p < 0.0001 (Fisher's exact test) compared to WT (Jackson et al, 2014). Animals were scored as either positive or negative for YFP expression, since animals at the L4 stage all showed similar YFP intensity.…”
mentioning
confidence: 99%
See 1 more Smart Citation